Buckling failure analysis of swing outrigger used in pump truck. (November 2019) - Zhao, Erfei; Lu, Yongneng; Cheng, Kai; Zhou, Liming; Sun, Wuhe; Meng, Guangwei
Abstract: Swing Outrigger is a type of slender thin-walled structure equipped in pump truck. It bears bending and shearing loads; thus, local buckling failure is apt to occur when pump truck is working. In this research work, both buckling load and ultimate load of swing outrigger used in pump truck is investigated. Firstly, two original outriggers' loading tests were conducted to obtain the actual buckling load and ultimate load. Afterwards, eigenvalue buckling analysis and nonlinear finite element analysis were carried out to investigate the theoretical buckling loads and ultimate loads. By comparing those results, it was found that FEM was verified effective to calculate the ultimate load and failure mode, but not effective to calculate the buckling load. After the swing outrigger was improved by increasing stiffeners, nonlinear finite element analysis and loading test were conducted again, and the results indicated that the carrying capacity of the improved outrigger has been raised greatly. Highlights: The failure reason of swing outrigger used in truck mounted concrete pump was studied. Eigenvalue buckling analysis was used to obtain theoretical buckling load and buckling mode. Nonlinear FEA was used to obtain theoretical failure load and failure mode. Buckling experiments of two original swing outriggers and one improved swing outrigger were conducted.